PENGARUH FAKTOR-FAKTOR KEDISIPLINAN TERHADAP PRESTASI KERJA PARA PEGAWAI DINAS PENDAPATAN KALIMANTAN TIMUR - HIDAYAT, MUCHTAR (Program Doktor Ilmu Ekonomi, 2010)
The location of this research is at Earning Department Office of East Borneo Province in Samarinda.The research problems is how is the supporting factors in work discipline of someone that consist of : prosperity, threat, resolutely, ability and the example of leader as free variable, it can influence work achievement that consist of : quality of work, quantity of work, reability and attitude as unfree variable.The research objectives is to know how is the influence of a whole work discipline factors toward work achievement of earning department employee of East Borneo Province and work discipline factors that has dominant influence toward work achievement of earning department employee of East Borneo Province.Based on the research toward 49 respondents it got result that a whole work discipline factors has positive influence toward work achievement that can see from the regression similarity, like this : Y = -0,6387 + 0,1011 X1 + 0,6693 X2 + 0,2573 X3 + 0,2312 X4 + 0,3598 X5. from the similarity above it indicated above threat (X2) = 0,6693 it very dominant toward work achievement.The conclusion is if work discipline factors involved prosperity, threat, resolutely, ability and the example of leader can be increase, so work achievement of Earning Department of East Borneo Province will be increase.Keywords: Â Â Discipline: prosperity, threat, resolutely, ability and the example of leader, and work achievement